Indirect network effects with two salop circles: the example of the music industry - Ralf Dewenter; Justus Haucap; Tobias Wenzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2009)
This paper analyses the interdependency between the market for music recordings and concert tickets, assuming that there are positive indirect network effects both from the record market to ticket sales for live performances and vice versa. Using a model with two interrelated Salop circles we show that prices in both markets are corrected downwards when compared to the standard Salop model. Furthermore, we show that the effects of file sharing on firms' profitability and on variety are ambiguous. File sharing can increase profits through increased concert ticket demand and thereby also lead to additional market entry and additional variety.
Keywords: L13; L82; Z10; 330; Music Industry; Indirect Network Effects; Salop Model; File Sharing; Musikwirtschaft; Preis; Network Externalities; Internet; Tausch; Theorie